2005
DOI: 10.1116/1.1978904
|View full text |Cite
|
Sign up to set email alerts
|

Growth optimization of GaAsSb lattice matched to InP by gas-source molecular-beam epitaxy

Abstract: Bulk GaAsSb samples were grown lattice matched to InP substrates at different temperatures using gas-source molecular-beam epitaxy in order to optimize the crystal quality. Growth temperatures from 15°C above the InP surface oxide desorption temperature to 145°C below it have been investigated. Undesirable properties such as Sb composition variation and natural composition superlattices in the growth direction have occurred at high growth temperature possibly due to phase separation. High quality, single phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, this is narrowest ever reported. 15,26 In addition, Raman scattering was employed, and the Raman spectra corroborated the PL results, which can provide an indication of the degree of alloy clustering and the miscibility gap. [22][23][24][25] Lastly, beryllium was used for the p-type doping of GaAsSb for transmission-line measurement (TLM) studies.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…To the best of our knowledge, this is narrowest ever reported. 15,26 In addition, Raman scattering was employed, and the Raman spectra corroborated the PL results, which can provide an indication of the degree of alloy clustering and the miscibility gap. [22][23][24][25] Lastly, beryllium was used for the p-type doping of GaAsSb for transmission-line measurement (TLM) studies.…”
Section: Introductionmentioning
confidence: 93%
“…16,17 By misorienting substrates, the optical and electrical properties of the epitaxial layers grown on GaAs surface are improved. 18,19 In respect to prior findings, [15][16][17][18][19][20][21] investigation on the effect of substrate tilting off the InP(100) orientation on the alloy uniformity and quality of GaAsSb is being proposed for the first time. GaAsSb alloys grown on InP(100) substrate by MBE and on InP (100) substrates tilted toward (111)A by 2 , 3 , and 4 off were characterized by x-ray diffraction (XRD) for crystallinity and photoluminescence (PL) for optical and crystalline quality.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the growth of GaAsSb is sensitive to the growth temperature, 4 two 300 nm GaAsSb samples, samples A and B with different growth temperature profiles were grown on InP substrates. The growth rate was determined by Ga flux and kept constant at 0.8 ML/ s. The growth temperature of sample A was raised from T d −30°C to T d + 10°C during growth, and sample B was grown with a reduced V/III ratio of ϳ70% of that of sample A and at a constant substrate temperature of T d − 35°C.…”
Section: Materials Growthmentioning
confidence: 99%
“…We have demonstrated that single phase, high quality GaAsSb lattice matched to InP can be grown at very low substrate temperature using gas-source molecular beam epitaxy ͑GSMBE͒. 4 In this study, high crystal quality GaAsSb was grown at a relatively high temperature in order to better match conditions for the growth of InP and related materials. The GaAsSb/ InP DHBTs grown by GSMBE technique with excellent f T near 350 GHz have been successfully developed.…”
Section: Introductionmentioning
confidence: 99%